Evaluation of the educational environments of undergraduate medicine and pharmacy programmes at the University of Zambia - Christian C Ezeala; Mary M Moleki (Tabriz University of Medical Sciences, 2018)
Background: Situational factors influence learners' approaches to learning and determine learning outcomes. The study determined issues in the learning environments of medical and pharmacy students at the University of Zambia with a view to providing information for improvement. Methods: A quantitative observational design based on the Dundee Ready Educational Environment Measurement (DREEM) inventory was used to survey undergraduate students' perceptions of their learning environments. A total of 270 students - 135 in years 3 to 7 of medical school and 135 in years 3 to 5 of pharmacy school - at the University of Zambia participated. Total, subscale, and single item DREEM scores were analysed and compared. Results: Mean total DREEM score for all participants was 119/200 (±20.4). Scores for the subscales varied from 15/28 (±3.6) for social self-perception to 21/32 (±3.9) for academic selfperception. The total and subscale scores were not significantly different between Medicine and Pharmacy at P > 0.05. Six areas of concern were observed in both programmes: lack of a social support system for stressed students, dictatorial staff, overemphasis on factual learning, tense teaching atmosphere, curriculum issues, and unpleasant accommodations. Medical students were particularly about tense classrooms and lack of feedback; pharmacy students were more likely to be concerned about curriculum issues. Conclusion: The study showed that although the educational climates of healthcare programmes in medical schools may be comparable, specific programme concerns can be significantly different. Strategic planning to improve schools should consider both general perceptions and specific issues in individual programmes.